(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article defines the essence of personal potential and its structure as a combination of the following three blocks of personal traits: motivational, stylistic, and instrumental. The structure of personal potential is considered: professional potential; working capacity potential; educational potential; creative potential; spiritual potential. The characteristics of an effective manager are given as a basis. The essence of managerial potential is characterized. The manager’s potential is presented in the article as a set of certain components: personal potential, emotional potential, cognitive potential, career potential, creative potential, leadership potential, communication potential. The article offers an interpretation of each element of managerial potential. It is noted that competencies are a functional tool for realizing managerial potential. To assess the level of competence development of the organization’s managers, it is proposed to use three components: professional, social, and conceptual competence. A list of components that an effective manager must possess and that testify to his readiness to develop his potential is proposed. The article suggests using D. Kolb’s learning models for managers to acquire new skills. For the maximum disclosure and development of managerial potential, the main areas of work in each organization have been developed. The article focuses on the role of managers, which are of fundamental importance for strategic changes and organizational productivity. It was determined that managers are the driving force in creating and opening new opportunities for the organization.